FUNDAMENTALS OF AGREEMENTS AND PEACE ACCORDING TO THE PERSPECTIVE OF FIQH SIYASAH RULES - Riyandi, Ahmad Febri; Abdullah Ulil Albab, Muhammad Maulana; Zamroni, Muhamad (AS-SAIS (JURNAL HUKUM TATA NEGARA/SIYASAH), 2025)
The rules of fiqh are very important guidelines for Muslims to solve a legal problem faced daily. Without these guidelines, Muslims cannot limit the permissibility or impermissibility of doing something, nor can they determine which action is preferable to doing or leaving. Muslims are bound by the rules and values they espouse, which are based on their religious teachings and good customs, when they act or behave. As for this research, the author has a goal so that readers know comprehensively related to existing problems and can solve these problems without contradicting according to the existing foundation. This research method uses the Literature Review Method which compiles the problems of a topic systematically, this research discusses problems related to the elements of the agreement and peace and the basis for resolving these matters, so that they are in accordance with existing laws, especially Fiqhiyah law, in this study the author also hopes that readers can broadly understand in carrying out the mathematics of the agreement or matters relating to peace.Keywords: Systematic, Method, Law, Treaty